Real time PCR for antemortem diagnosis in humans and high throughput rabies virus screening - Zarate-Segura, P.; Bastida-Gonzalez, F.; Ellison, J.; Gallardo-Romero, N.; Loparev, V.; Velasco-Villa, A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is one of the oldest and most devastating diseases, typically a 100% case mortality rate. Antemortem rabies diagnosis in humans is important to institute infection control procedures and avoid further exposures of health personnel and other people who may have been in contact with saliva of the patient, to determine epidemiologically if other individuals were exposed to the same source, to monitor disease progression during experimental therapeutic interventions, to prevent cross infection during organ transplantation, and if negative, to examine other differential diagnoses. Four samples are recommended for antemortem testing of rabies in humans (saliva, serum, nuchal skin biopsy and cerebrospinal fluid) in which antibodies, viral antigens and nucleic acids are detected using neutralization, indirect and direct immunofluorescence and reverse transcription PCR methods. The turnaround time to provide conclusive results on all four samples analyzed by all techniques is approximately 24 to 48 hrs. Real time PCR appears to be one promising technique to expedite results on nucleic acid detection and accurately quantitate viral loads in patient samples. However, there is no universal primer or probe that may detect the broad lyssavirus diversity described to date, which decreases the sensitivity of the test dramatically. The objective of this study was the design of a sensitive and specific real-time PCR assay to detect and quantitate a broad variety of rabies viruses in antemortem and postmortem samples from human/animal tissues and bodily fluids.